Promoting Factors to Stay at Work Among Employees With Common Mental Health Problems: A Multiple-Stakeholder Concept Mapping Study - van Hees, Suzanne G. M.; Carlier, Bouwine E.; Blonk, Roland W. B.; Oomens, Shirley (Frontiers in Psychology, 2022)
Most individuals affected by common mental health problems are employed and actually working. To promote stay at work by workplace interventions, it is crucial to understand factors perceived by various workplace stakeholders, and its relative importance. This concept mapping study therefore explores perspectives of employees with common mental health problems (n=18), supervisors (n=17) and occupational health professionals (n=14). Per stakeholder group, participants were interviewed to generate statements. Next, each participant sorted these statements on relatedness and importance. For each group a concept map was created, using cluster analysis. Finally, focus group discussions were held to refine the maps. The three concept maps resulted in several clustered ideas that stakeholders had in common, grouped by thematic analysis into the following meta-clusters: A) Employee’s experience of autonomy in work (employee’s responsibility, freedom to exert control, meaningful work), B) Supervisor support (being proactive, connected and involved), C) Ways to match employee’s capacities to work (job accommodations), D) Safe social climate in workplace (transparent organizational culture, collective responsibility in teams, collegial support), and E) professional and organizational support, including collaboration with occupational health professionals. Promoting Stay at work is a dynamic process that requires joined efforts by workplace stakeholders, in which more attention is needed to the interpersonal dynamics between employer and employee. Above all, a safe and trustful work environment, in which employee’s autonomy, capacities and needs are addressed by the supervisor, forms a fundamental base to stay at work.